Prospects and Challenges of Green Hydrogen Economy via Multi-Sector Global Symbiosis in Qatar - Eljack, Fadwa; Kazi, Monzure-Khoda (Frontiers in Sustainability, 2021)
Low carbon hydrogen can be an excellent source of clean energy, which can combat global climate change and poor air quality. Hydrogen based economy can be a great opportunity for a country like Qatar to decarbonize its multiple sectors including transportation, shipping, global energy markets and industrial sectors. However, there are still some barriers to the realization of a hydrogen-based economy, which includes large scale hydrogen production cost, infrastructure investments, bulk storage, transport & distribution, safety consideration, and matching supply-demand uncertainties. This paper highlights how the aforementioned challenges can be handled strategically through a multi-sector industrial-urban symbiosis for the hydrogen supply chain implementation. Such symbiosis can enhance the mutual relationship between diverse industries and urban planning by exploring varied scopes of multi-purpose hydrogen usage (i.e., clean energy source as a safer carrier, industrial feedstock and intermittent products, vehicle and shipping fuel, international energy trading, etc.) both in local and international markets. It enables individual entities and businesses to participate in the physical exchange of materials, by-products, energy, and water, with strategic advantages for all participants. Besides, waste/by-product exchanges, several different kinds of synergies are also possible, such as the sharing of resources and shared facilities. The diversified economic base, regional proximity and the facilitation of rules, strategies and policies may be the key drivers that support the creation of a multi-sector hydrogen supply chain in Qatar